The nation/state according to Zygmunt Baumann - حربه, أمل; عفراء اسماعيل (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Solid modernity made man the ultimate goal of liberation, so it raised the esteem of the mind, and announced its revolution for renewal and modernization of the various aspects of life. It also announced a break with the past. Its impact was not only exporting the products of the technological revolution, but also attempts to deconstruct some religious and metaphysical beliefs, amazing developments in modern physics, and the rise of the nation/state as the only dominant model of government that made birth the basis of its sovereignty. The emergence of the modern state coincided with the emergence of homeless people without a state, the idea of ​​social nudity emerged, and the law of the forbidden man was resurrected, but with liquid modernity, as the Polish philosopher Zygmunt Bauman sees, the affair over centuries between the nation and the state turned into an intercourse that dissolves The place of the sacred marital relationship, for their entry into the free world in the Organization for Economic Cooperation and Development. Keywords: the nation/state _ social nudity _ Homo Sacer _ the technological revolution _ liquid modernity.